R-IEDs Technology for NCRE, Telework and Environmental Impact Mitigation - Sandoval-Ruiz, Cecilia E. (2020)
In this research, a mathematical model was developed for the application of R-IEDs technology on FPGAs in configurable power systems, aimed at supporting renewable energies, teleworking and mitigating environmental impact. The scheme is oriented to the design of regenerative systems, with cycles of reuse, recycling, dynamic reconfiguration and feedback of by-products or energy, in correspondence with the circular model. The proposed method is based on a study of environmental impact factors and technological alternatives, for the design and configuration of intelligent electronic devices, in a distributed scheme, based on FPGA for dynamic updating. Among the results is the technological proposal developed for the integration of renewable energies, through remote activities in the energy sector, waste heat recovery and fractal simplification based on scalable models. This allows us to conclude on the high flexibility and efficiency of the model by applying technological tools aimed at mitigating the environmental impact and sustainable engineering.